Minimally invasive thyroid anaplastic carcinoma with long survival - ERBARUT SEVEN, İPEK; GÜLLÜOĞLU, MAHMUT BAHADIR; UĞURLU, MUSTAFA ÜMİT; YEGEN, ŞEVKET CUMHUR (TURKISH SURGICAL ASSOC, 2018)
Anaplastic thyroid carcinoma is a highly lethal malignancy. Previously, only five cases of a noninvasive form of anaplastic thyroid carcinoma with excellent prognosis were reported, We report a case of a 68-year-old man who presented with a 3,8 cm thyroid nodule diagnosed by fine needle aspiration biopsy as poorly differentiated spindled and epithelial malignant cells, Lobectomy and isthmusectomy were performed, and the final diagnosis was micro-invasive anaplastic thyroid carcinoma arising in a poorly differentiated carcinoma, The patient remains disease-free after six years, even after hemithyroidectomy and radiation treatment. Noninvasive/micromvasive anaplastic thyroid carcinoma appears to be a different disease entity from classical anaplastic thyroid carcinoma, with favorable prognosis and long disease-free survival.
Keywords: Thyroid; anaplastic thyroid carcinoma; microinvasion; SINGLE INSTITUTION; CHEMOTHERAPY; SURGERY; CANCER